Analisis Perbandingan Biaya dan Waktu pada Penggunaan Duct Spacer dengan Prefabricated dan Hollow Baja Ringan Untuk Pekerjaan Underground Ducting : Studi Kasus Pekerjaan Underground Ducting Untuk Instalasi Airfield Lighting System di Bandara Dhoho Kediri, Jawa Timur - Ali Masrodin; Albani Musyafa; Fitri Nugraheni; Taufik Dwi Laksono (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The Kediri Airport development project encountered challenges related to underground ducting work. The design of Kediri Airport adheres to international standards, which led to the use of materials not readily available in Indonesia, specifically pipes and duct spacers. Duct spacers are tools used to arrange ducting pipes according to their formation and prevent them from floating during concrete pouring due to buoyancy. The SKEP/114/VI/2002 serves as a reference for underground cable installation, involving direct burial of cables at a depth of 70 cm, covered with a 5 cm layer of sand above the cable surface. These two approaches significantly differ, necessitating problem-solving solutions. To address this issue, research was conducted to find suitable duct spacers in Indonesia. Two alternative materials were considered: PVC and lightweight hollow steel. The study compared costs and time associated with these materials. PVC duct spacers would be imported and be fabricated in Indonesia, while hollow steel duct spacers would be fabricated on-site. The research focused on three aspects: ducting work methods, duct spacer design, and cost-time analysis. Given tight installation spaces and busy schedules, duct spacers needed to be compact, simple, and adaptable to various pipe formations. The design for hollow steel duct spacers aimed for simplicity to reduce on-site construction work. However, care was taken to avoid potential injuries from exposed bolts on the hollow steel frame. The PVC duct spacer design utilized Polytam PF 1000 material, with a nominal shear strength of 399 kg and a nominal moment of 266 kg·cm—sufficient to withstand saturated soil loads up to 162 cm but not vehicular loads. Analyzing procurement time, PVC duct spacers from Indonesian manufacturers were the quickest, taking only 56 days due to no port clearance delays. The fastest completion time for the project was achieved using PVC duct spacers, taking 122 seconds—three times faster than hollow steel duct spacers. While lightweight steel was the most cost-effective option for on-site procurement, combining cost and time analysis favored PVC duct spacers. The minimal cost difference allowed for accelerated production, minimizing the risk of delays